2022
DOI: 10.1021/acs.jmedchem.2c00190
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Gankyrin Inhibition as a Therapeutic Strategy for Breast and Lung Cancer

Abstract: Gankyrin is an oncoprotein responsible for the development of numerous cancer types. It regulates the expression levels of multiple tumor suppressor proteins (TSPs) in liver cancer; however, gankyrin’s regulation of these TSPs in breast and lung cancers has not been thoroughly investigated. Additionally, no small-molecule gankyrin inhibitor has been developed which demonstrates potent anti-proliferative activity against gankyrin overexpressing breast and lung cancers. Herein, we are reporting the structure-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Evidence from studies on the transcriptional activity of the tumor suppressor gene p53 suggests that gankyrin has a negative regulatory effect on it 4 , 27 . To confirm this, we tested the effects of siRNA against gankyrin on the expression of p53 in Hs578T and MB-MDA-231 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from studies on the transcriptional activity of the tumor suppressor gene p53 suggests that gankyrin has a negative regulatory effect on it 4 , 27 . To confirm this, we tested the effects of siRNA against gankyrin on the expression of p53 in Hs578T and MB-MDA-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has been presented to demonstrate its influence on multiple cancer-related pathways in various types of cancer. An elevation of gankyrin leads to the destruction of tumor suppressor proteins, resulting in an uncontrolled growth of cancer cells 27 . Our study revealed a significant increase in gankyrin expression in TNBC cells, indicating its critical role in the proliferation and growth of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented to demonstrate its in uence on multiple cancer-related pathways in various types of cancer. An elevation of gankyrin leads to the destruction of tumor suppressor proteins, resulting in an uncontrolled growth of cancer cells 24 . Our study revealed a signi cant increase in gankyrin expression in TNBC cells, indicating its critical role in the proliferation and growth of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies on the transcriptional activity of the tumor suppressor gene p53 suggests that gankyrin has a negative regulatory effect on it 4,24 . To con rm this, we tested the effects of siRNA against gankyrin on the expression of p53 in Hs578T and MB-MDA-231 cells.…”
Section: Gankyrin Negatively Regulates the Expression Of P53 In Tnbc ...mentioning
confidence: 99%